2019
DOI: 10.30997/ijsr.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Activities of MGMP Ipa Activities to Increase the Teacher Competence in Bogor District

Abstract: MGMP is a community of teachers to always learn (long life learning). Rapid development of the times requires the teacher to participate in the pursuit of knowledge. Lifelong learning is the teacher's obligation to generate knowledge. This is necessary because the teacher is a facilitator of students to gain knowledge. In line with that, teachers are expected to master every change process so students can also face global challenges. These results indicate that the majority of teachers who come to MGMP IPA Bog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…(Interview, Mr. A, 12 May 2020) From that statement, the participant shows that MGMP is a helpful organization for them to share and discuss anything that positively impacts their TPD. Hayu et al (2019) also found that the discussion and sharing in the teacher forum would positively increase teacher professionalism. Therefore, it might help them find a new method to be used in their class by having discussions and sharing experiences.…”
Section: Mgmp Roles To Tpdmentioning
confidence: 89%
See 1 more Smart Citation
“…(Interview, Mr. A, 12 May 2020) From that statement, the participant shows that MGMP is a helpful organization for them to share and discuss anything that positively impacts their TPD. Hayu et al (2019) also found that the discussion and sharing in the teacher forum would positively increase teacher professionalism. Therefore, it might help them find a new method to be used in their class by having discussions and sharing experiences.…”
Section: Mgmp Roles To Tpdmentioning
confidence: 89%
“…However, there are 4% STD and 2% D. Those data show that most of the MGMP members already collaboratively and communicatively with the other members. Further, the teacher collaboration would give positive results in the TPD improvement (Hayu, Permanasari, Sumarna & Hendayana 2019). Kent (2018) also found that the sharing of each member such as, share the links of educational journals, conferences, materials, and scholarships helps the teacher to increase the motivation in teaching and the TPD.…”
Section: Mgmp Roles To Tpdmentioning
confidence: 99%
“…as well as continuous outreach (Susetyo, 2020). Even though every maximum learning will produce a good outcome for the implementation of education (WRR Hayu et al, 2019;2023;HT Adri, 2021).…”
Section: Introductionmentioning
confidence: 99%